Experimental evaluation of nucleate pool boiling heat transfer correlations for R245fa and R1233zd(E) in ORC applications. (March 2020) - Welzl, Matthias; Heberle, Florian; Brüggemann, Dieter
Abstract: In binary geothermal power plants based on the Organic Rankine Cycle (ORC) typically shell-and-tube heat exchangers are used as evaporators. In the shell-side, nucleate boiling of the working fluid takes place on the external surfaces of tubes. For the replacement of fluids with high global warming potential (GWP) or selection of efficient working fluids, a comprehensive evaluation has to be performed. Therefore, the knowledge about the nucleate pool boiling heat transfer coefficient (HTC) in combination with the electrical power output is necessary. In this study, the focus is led on the experimental evaluation of nucleate pool boiling heat transfer correlations for R245fa and its possible replacement R1233zd(E) in ORC applications. The nucleate boiling HTC on a horizontal tube and the electrical power generation of a 1 kW scroll expander are simultaneously measured with an ORC test rig for both fluids. The thermal input is provided by an electrically heated preheater and evaporator. Nucleate boiling takes place on a plain copper tube with an outer diameter of 32 mm and a heated length of 822 mm. The surface temperature of the copper tube is determined by thermocouples within the tube in consideration of thermal conduction. The obtained measurement results, regarding heat transfer characteristics as well as power output, show that the working fluid R245fa performs better at equal saturation temperatures due to the higher density and saturation pressure, and the lower viscosity. The HTC for R245fa is up to 43.2% higher in comparison to R1233zd(E). The experimental HTC are compared to selected nucleate pool boiling HTC correlations. The evaluation reveals that correlations according to Cooper and Gorenflo et al. show the slightest mean absolute deviations between 4.75% and 15.65% for both working fluids. Highlights: An evaluation of HTC correlations is presented to assess their prediction accuracy. Nucleate pool boiling HTC and power of scroll expander are simultaneously measured. R245fa performs better than R1233zd(E) at equal saturation temperatures. Cooper and Gorenflo correlations show the slightest deviations.